(untitled) (Labor and Human Development Law Journal, 2018)
This essay aims to reflect on psychosomatic diseases in the work environment. Psychosomatic illnesses, among them depression, are the great evils that affect our society today. Depression is characterized by the loss or diminution of interest and pleasure in life, generating anguish and prostration, a symptom of permanent melancholy. This disease can be developed for a number of reasons, but in today’s society it has been perceived and noticed more frequently and often associated with work. Psychiatric illnesses are ignored by many companies, who do not recognize their gravity and see them only as a transient emotional situation or as a lack of personal disposition for work, using the well-known practice of blaming the victim his or herself. This essay aims at analyzing the possibility of characterizing depression as a work disease, trying to delimit the extent to which illness and work affect one another, in a relation of cause and effect, highlighting the main aspects related to the existing knowledge on depression, especially in the work environment. Thus, the method employed is the deductive dialectic, based on the analysis of data that inform the seriousness of the problem, its treatment in the legal, doctrinal and jurisprudential contexts, in light of the social reality brought forth by the new generation known as technological and informational, in which human values from the past have become less important, especially in relation to the reality of capital. This liquidity of social understanding, especially by the employer, launches a great challenge for the protection of the sick person and for the realization of their fundamental guarantees in the working environment. KEYWORDS: Depression. Work environment. Psychological disorder. Legal protection to the worker. Work Sickness.